2017
DOI: 10.1016/j.jaut.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of impending disease flare in African-American systemic lupus erythematosus patients

Abstract: Immune dysregulation in systemic lupus erythematosus (SLE) contributes to increased disease activity. African American (AA) SLE patients have an increased prevalence of complications from disease flares and end-organ damage that leads to increased morbidity and early mortality. We previously reported alterations in inflammatory and regulatory immune mediator levels prior to disease flare in European American (EA) SLE patients. In the current study, we assessed baseline and follow-up plasma levels of 52 soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 44 publications
2
32
2
Order By: Relevance
“…Previous investigators have reported that chemokines took part in inflammation via attracting T cells in the target organ (Cao et al 2003;Liao et al 2017). Moreover, increased levels of chemokines in SLE were well confirmed (Wong et al 2008;Munroe et al 2017), and might lead to the accumulation of IL-35 in renal tissue. This, in part, may explain the decrease in serum concentrations of IL-35 in LN patients.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous investigators have reported that chemokines took part in inflammation via attracting T cells in the target organ (Cao et al 2003;Liao et al 2017). Moreover, increased levels of chemokines in SLE were well confirmed (Wong et al 2008;Munroe et al 2017), and might lead to the accumulation of IL-35 in renal tissue. This, in part, may explain the decrease in serum concentrations of IL-35 in LN patients.…”
Section: Discussionmentioning
confidence: 80%
“…Production of autoantibody and immune complex deposition with subsequent infiltration of inflammatory cells, and perturbed cytokine activities are central to both onset and progression of renal pathology (Waldman and Madaio 2005;Rahman and Isenberg 2008;Munroe et al 2017). Furthermore, it has been suggested by several studies that regulatory T cells (Treg), as well as its associated cytokines such as interleukin , play a pivotal role in the progression of SLE (Valencia et al 2007;Bonelli et al 2008;Tselios et al 2014;Cai et al 2015a, b).…”
Section: Introductionmentioning
confidence: 99%
“…In a large, longitudinal cohort of pediatric SLE patients, Banchereau and colleagues [18] identified transcriptional modules that change over time with disease activity and identify clinical subsets of pediatric SLE patients. In addition, our group has identified soluble mediators, including cytokines, chemokines, adhesion molecules, and soluble receptors that associate with risk of SLE disease flare [19,20]. Although the specific pathways that distinguish an impending disease flare differ somewhat between European American and African American cohorts and likely vary between individual patients, an assay that simultaneously surveys multiple immune pathways accurately identified SLE patients at higher risk of future enhanced disease activity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A combined soluble mediator score incorporating 52 analytes was increased in patients with impending flare compared to either matched stable patients or the same patients during a clinically stable period. 44, 45 This score accurately predicted flare in both European American and African American study groups. Accurate prediction of SLE flare may allow early treatment or prevention of flares.…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 87%